ONLINE LEARNING DURING COVID-19 PANDEMIC: PROBLEMS FACED BY MIDWIFERY STUDENTS OF STIK BINA HUSADA PALEMBANG AND SUGGESTIONS TO ENHANCE EFFECTIVENESS - Agus Wahyudi (Language and Education Journal, 2021)
COVID-19 or widely known as Corona Virus Disease 2019 influences the teaching and learning process in the world. Due to prevent the spread of the virus, the Ministry of Education and Culture asks the teachers to teach the students using online learning. Therefore, this study aimed to find out the problems faced by the midwifery students of STIK Bina Husada Palembang and suggestions to enhance the effectiveness of online learning. Descriptive research was applied. There were 35 students involved in this research, namely Midwifery students of STIK Bina Husada Palembang in the academic year of 2020/2021. The data were collected using a questionnaire and were analyzed qualitatively with an interactive model, covering data collection, data reduction, presentation, and conclusion. Having implemented online learning during the Covid-19 Pandemic, the students, parents, and teachers got problems with online learning. The problems can be overcome by implementing some suggestions mentioned in this research.